Internal Control Practices of Readymade Garments Sector (Textile Industry) in Bangladesh - Saha, Anup Kumar; Mondal, Kartik Chandra (Asian Business Review, 2012)
Internal control has a pivotal role in ensuring sustenance of any industry because it plays an important role in preventing and detecting fraud and protecting the organization's resources. This study has found many factors that are relevant for internal control practices in readymade garments (RMG) sector. These vary from maintenance of employees’ job description to bonding employees with special access. In many variables these companies are practicing acceptable level of internal control, while in some they are not doing so good and have ample scope to improve that level. RMG sector is mainly populated with sole proprietorship firms and they do not allocate much resource to such practice. Even then the concern for internal control has to be implemented to ensure long lasting role in the economy.